The novel and the American left : critical essays on Depression-era fiction - Casey, Janet Galligani (University of Iowa Press, 2004)
The first collection of critical essays to focus specifically on the fiction produced by American novelists of the Depression era, The Novel and the American Left contributes substantially to the newly emerging emphasis on twentieth-century American literary radicalism. Recent studies have recovered this body of work and redefined in historical and theoretical terms its vibrant contribution to American letters.